Pengaruh Brand Trust dan Brand Image terhadap Keputusan Pembelian pada Usaha Rental Multimedia: Studi Kasus pada Konsumen Omah Visual Malang - Bobyvio Mirza Lavfidi (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
The rapid growth of the digital content creation industry has intensified competition in the multimedia rental sector, making brand management a critical factor for business sustainability. This study aims to analyze the influence of Brand Trust and Brand Image on Purchase Decision at Omah Visual Malang. The research employed a quantitative explanatory approach with data collected from 90 respondents using accidental sampling. Data were analyzed through multiple linear regression, coefficient of determination, and hypothesis testing (t-test and F-test). Results indicated that the multiple regression equation was Y' = 3.271 + 0.321X1 + 0.574X2 + e. The coefficient of determination yielded an adjusted R-square of 0.689, indicating that Brand Trust and Brand Image jointly explained 68.9% of the variance in Purchase Decision. Partial tests showed that Brand Trust (tₙₐᵗ = 2.871, sig. = 0.005) and Brand Image (tₙₐᵗ = 6.730, sig. = 0.000) each had a significant positive effect on Purchase Decision. The simultaneous test confirmed that both variables together significantly influenced Purchase Decision (Fₙₐᵗ = 99.479, sig. = 0.000). Brand Image demonstrated a stronger influence than Brand Trust. Omah Visual Malang is advised to strengthen its brand distinctiveness and expand its product range to enhance consumer confidence and purchase decisions.